Densidade de estocagem sobre o desempenho zootécnico, cortisol plasmático e custo na larvicultura intensiva do pirarucu (Arapaima gigas) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Inadequate stocking density in fish larviculture can cause dominance behavior that harms the feeding, resulting in stress, high number of heterogeneous fish and low productive rates. The aim of this study was to evaluate the effect of stocking densities on growth performance, cortisol plasmatic level and partial cost of pirarucu larviculture production. We used 900 pirarucu larvae (1.32 ± 0.25 g; 5.90 ± 0.33 cm) trained to feed inert diet. Fish were stocked at densities of 400; 800; 1200; 1600 and 2000 larvae.m-3 and housed in 15 tanks (50 l; n = 3), in a recirculating water system and constant aeration in a completely randomized design. Larvae were fed with extruded commercial diet (45% of crude protein; Nutripiscis STARTER – Presence®, 0.8 mm) in the proportion of 10% of the biomass, divided into eight meals a day, for 30 days. At the end of the trial period, fish were measured and weighed; four fish per tank were euthanized for analysis of plasma cortisol. Data were subjected to one-way ANOVA and Tukey test (5%). Finally, the partial cost of pirarucu larviculture production was calculated. Pirarucu larvae kept in density of 400 larvae.m-3 showed high mortality rate (76.67%), with the poorest results in productivity and highest production cost. Fish reared in the density of 2000 larvae.m-3 presented voracity during feeding, survival rate of 93.33%, and the highest zootechnical performance: final weight (12.16 ± 0.89 g), weight gain (10.84 ± 0.89 g) and relative growth rate (7.69 ± 0.26%). The relation between stocking density and cortisol levels was inversely proportional, indicating higher levels of stress for fish reared at low density (400 larvae.m-3), which reflected on the zootechnical parameters as the final weight (6.41 ± 0.77 g), weight gain (5.09 ± 0.76 g) and relative growth rate (4.61 ± 1.28%). Larvae stocked at 2000 larvae.m-3 showed reduced production cost (R$ 6.54) and consequently higher revenues per larvae (R$ 5.42). For pirarucu larviculture (5-10 cm), we recommend to use 2000 larvae.m-3, which results in higher survival and growth performance, obtaining higher and homogeneous fish with a lower production cost.
Keywords: Carnívoros; Cortisol; Paiche; Peixes amazônicos; Produtividade da piscicultura; CIÊNCIAS AGRÁRIAS: ZOOTECNIA: PRODUÇÃO ANIMAL: MANEJO DE ANIMAIS; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA: AQUICULTURA: PISCICULTURA